Big book of Just so stories - Álvarez,Marta (Thaxted, Essex Miles Kelly Publishing, 2016)
Big Book of Just So Stories is a delightful compendium for children aged 3+, presenting four of Rudyard Kipling's brilliantly funny Just So Stories across large format pages of full-bled artwork scenes. Every page showcases beautiful illustrations packed with charm and detail that will enthrall younger children. They have been carefully retold to appeal to younger readers, and the book has been produced on thicker paper to help little hands turn each page more easily
Keywords: Big book of short stories